Inferring Trade Direction From Intraday Data. - Lee, Charles M C; Ready, Mark J (Journal of Finance, 1991)
This paper evaluates alternative methods for classifying individual trades as market buy or market sell orders using intraday trade and quote data. The authors document two potential problems with quote-based methods of trade classification: quotes may be recorded ahead of trades that triggered them, and trades inside the spread are not readily classifiable. These problems are analyzed in the context of the interaction between exchange floor agents. The authors then propose and test relatively simple procedures for improving trade classifications.